Gender Gaps and the Role of Bosses - Felix Holub; Moritz Drechsel-Grau (ZBW - Leibniz Information Centre for Economics, 2021)
This paper investigates the contribution of managers to gender gaps and analyzes whether the over-representation of men in management positions puts women at a disadvantage. Relying on personnel data from one of the largest European manufacturing firms, we separate out the factors explaining gender gaps. Adjusted pay gaps are positive, which means that men earn more than observationally equivalent women. A significant share of pay gaps can be explained by the sorting of men and women to different managers. More importantly, gender gaps in bonus payments causally depend on the manager's gender. Accounting for worker and manager heterogeneity, bonus gaps are larger when the manager is male. This is driven by the fact that performance ratings are more favorable to men if handed out by a male manager. We present suggestive evidence that the relevance of manager gender for pay gaps is driven by discrimination rather than same-gender complementarities in productivity. However, independent of the root cause of these differences in evaluations by manager gender, the findings imply that a lower number of female managers increases gender gaps and thus constitutes a structural disadvantage for women.
Keywords: J16; J31; J33; J71; M5; D83; 330